Prevalence, sociodemographic determinants and self-reported reasons for hysterectomy in India - Chander Shekhar; Balram Paswan; Abhishek Singh (BMC, 2019)
Abstract Background Evidence of hysterectomy in India is limited mainly due to lack of information in large-scale nationally representative health surveys. In 2015-16, the fourth National Family Health Survey (NFHS-4) - a cross-sectional survey - collected for the first time direct information on hysterectomy and self-reported reasons for undergoing the procedure among women in the reproductive age group. This paper examines the prevalence and determinants of hysterectomy in India among women aged 30-49 years in 29 states and seven union territories (UTs) of India using the NFHS-4 dataset. Methods Percentage weighted by sampling weights was used for estimating the prevalence of hysterectomy. The paper used crosstabulations and percentage distributions to estimate the prevalence of hysterectomy across different socioeconomic backgrounds and reasons for undergoing hysterectomy respectively. A multivariate binary logistic regression model was also used to find statistically significant determinants of hysterectomy. Results In India as a whole, 6 % of women aged 30-49 years had undergone a hysterectomy. The percentage of women who had undergone the procedure was found to vary considerably across the states and the UTs (from a minimum of 2% in Lakshadweep to a maximum of 16% in Andhra Pradesh). A noticeable fact that emerged was that the majority of the hysterectomies were performed in the private sector except in the northeast region. Years of schooling, caste, religion, geographic region, place of residence, wealth quintiles, age, parity, age at first cohabitation, marital status, and body mass index of women were found to be the sociodemographic determinants statistically associated with hysterectomy in India. The reasons reported frequently for hysterectomy were excessive menstrual bleeding/pain (56%), followed by fibroids/cysts (20%). Conclusion The percentage and likelihood of undergoing hysterectomy are relatively high among women from older age groups (45-49), those who reside in rural areas, those without schooling, those who are obese, those having high parity, those with a low age at first marriage, and those who reside in the eastern and southern parts of India. The policy implication of these findings is that the reproductive health program managers should ensure regular screening and timely treatment of the problems resulting in hysterectomy.